Evaluación de compuestos químicos que proporcionen propiedades hidrofóbicas a textiles de algodón para Saint Germain Ltda, a nivel laboratorio (2018)
In this project were evaluated chemical compounds that give hydrophobic properties to cotton textiles. The coating formulation were made on a laboratory scale. A reverse engineering process was performed on a commercial hydrophobic textile product. Subsequently, chemical compounds were selected to intend to use as a coating on the textile. After the experimental design and the evaluation of each sample with the drop test, standardized wash cycles were performed to determine the coating resistance. Through the washing resistance tests and the contact angle measurements, it was determined which compounds give better properties and which maintain them after the washing cycles. Finally, the approximate production cost of the best option selected previously was calculated. In this way, it is left to the company's criteria to use this or another alternative for the purposes of its production processes.